AQIDAH DAN BUDAYA: UPAYA MELIHAT KORELASI AGAMA ATAU BUDAYA DALAM MASYARAKAT - Wage Wage (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2016)
This paper will try to review the special problems of religion in the aqidah is faced with a growing culture of trust in our society today. Although it has experienced a shift towards the establishment and implementation of the values to Islamization in this case is a creed, but not necessarily completely eroded confidence entrenched culture of our ancestors. It is important to understand and inculcate the belief in the values of a civilized society, because Islam itself is very appreciative of cultural values, even culture is one tool to spread the religion in a historical context. So that people can discover the truth aqidah as guidance in religious community life and culture. That is, people who are subject to the rule of God, the people who have social ties of kinship and community ties and strong cultural religiosity.